2008
DOI: 10.4103/0970-0358.44932
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation-coupled bipolar cautery unit: A practical, economical, and simple version

Abstract: Hemostasis is a fundamental principle of surgery for which electrocoagulation is universally used. Bipolar electrocautery has an advantage over monopolar electrocautery in terms of the precision of the extent of tissue coagulation and the lateral extent of thermal tissue injury. However, secondary to the thermal changes induced in the tissue due to electric current passage, there is charring of tissue, which adheres to the cautery tip. This, not only decreases its effectiveness, but also, by getting avulsed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Tools and materials that can be used in its manufacture include bipolar electrocautery, sterile strips, infusion fluids (NaCl 0.9%), infusion hoses, and scissors. The stage in making it is cut at the end of the infusion hose by removing the rubber part and then on the other side it is inserted into the infusion fluid [30]. Fixation of the end of the infusion hose is carried out using sterile strips on the outer side of the end of the electrocautery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tools and materials that can be used in its manufacture include bipolar electrocautery, sterile strips, infusion fluids (NaCl 0.9%), infusion hoses, and scissors. The stage in making it is cut at the end of the infusion hose by removing the rubber part and then on the other side it is inserted into the infusion fluid [30]. Fixation of the end of the infusion hose is carried out using sterile strips on the outer side of the end of the electrocautery.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation of the end of the infusion hose is carried out using sterile strips on the outer side of the end of the electrocautery. In its use for a year, it was reported that using a combination of electrocautery and infusion fluid simultaneously resulted in a decrease in tissue adhesion/adhesion, tissue scorching, the formation of surgical fumes, and enhancing the coagulation effect of tissues [28]- [30].…”
Section: Discussionmentioning
confidence: 99%